Comparison of clinical and para-clinical characteristics between children and adults with the Omicron variant of COVID-19 - Yuchen Peng; Yufei Shi; Wentao Zhu; Xiaopeng Li; Jiwei Fu; Xincheng Wu; Pei Shi; Xiaoping Wu (Journal of Infection in Developing Countries)
Introduction: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) Omicron variant is associated with higher transmissibility, but lower disease severity, compared to some other variants. However, its exact pathogenicity among children is still largely unknown. This study was conducted to determine the differences in clinical characteristics between children and adults infected with this variant.